Deficiency Pattern and Responsiveness in Clinical Settings in Discovering the Correlation between Vitamin D Analogues and Hair Growth in Alopecia Areata - Adeeba Ahmad, Nabeela Kanwal, Ayesha Jamil, Muhammad Ikram Ul Haq, Shandana Altaf, Naveed Lodhi (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Alopecia areata (AA) is an autoimmune disorder characterized by patchy hair loss, often linked to vitamin D deficiency, which plays a crucial role in the regulation of hair follicle cycling. Objective: To evaluate the level of serum vitamin D in Alopecia areata (AA) patients, as well as the relationship between the condition’s severity and the effectiveness of vitamin D analogues in these individuals. Methods: A randomized control study was conducted using non-probability consecutive sampling, including 143 patients. The AA was diagnosed through clinical and dermoscopic features, along with the SALT score calculation. Serum vitamin D levels and baseline demographics were recorded for each patient. For one year, 0.005% calcipotriol was applied topically twice daily. Patients were followed up with every month, and a concluding SALT score was assessed at the termination of the study to evaluate treatment effectiveness. A p-value of less than 0.05 was considered significant. Results: The mean age of the participants was 31.2 ± 8.9 years, with 58% female and 42% male. After six months, the mean SALT score dropped from 21.2 ± 5.8 at baseline to 9.7 ± 3.2. Serum vitamin D levels were low in 99 out of 143 individuals (69.2%). Using SALT50 as a metric of effectiveness, topical calcipotriol was found to be beneficial in 101 patients (70.6%) overall. Conclusion: AA patients have considerably lower serum vitamin D levels, and its analogues can help grow more hair, significantly reducing the severity of AA. Keywords: Alopecia areata; Calcipotriol; SALT score; Vitamin D deficiency.